2006
DOI: 10.3137/ao.440305
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing snowmelt variability in a land‐surface‐hydrologic model

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 42 publications
(32 reference statements)
1
29
0
Order By: Relevance
“…Within the models examined here, only two papers illustrated the effects of late-lying snow drifts (Davison et al, 2006;Pomeroy et al, 2007). In both studies, the areas of interest were relatively small.…”
Section: Does the Model Capture The Spatial And Temporal Scales Of Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the models examined here, only two papers illustrated the effects of late-lying snow drifts (Davison et al, 2006;Pomeroy et al, 2007). In both studies, the areas of interest were relatively small.…”
Section: Does the Model Capture The Spatial And Temporal Scales Of Inmentioning
confidence: 99%
“…Some papers consider the modelling of physical processes relevant to low flows, such as Moore (1993) for glacierized basins, Stadnyk et al (2005) for groundwater contributions to flow, and Davison et al (2006) and Pomeroy et al (2007) for latelying snow drifts, but none of these studies explicitly consider the capability of the models to predict lowflows. A number of other case studies also make use of hydrologic models coupled with groundwater models (e.g., Wardlaw et al, 1994;Abbey et al, 2007;Ford and Wexler, 2007;and AquaResource, 2008) or just groundwater models (e.g., Clausen and Rasmussen, 1993;Clausen et al, 1994;Lanen et al, 1993) for water management purposes, but again the focus was not specifically on low-flows.…”
Section: Low-flow Studies Using Deterministic Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Failure to account for even basic features such as slope and aspect has been shown to be detrimental to snowmelt and stream flow prediction (Dornes et al, 2008a). In modelling a sub-Arctic catchment, Davison et al (2006) concluded that incorporating surface slope and aspect is required for proper snow-cover ablation and runoff timing. Pohl et al (2006) identified that the small-scale variability in solar radiation for the melt period was an important contributing factor for the development of patchy snow cover in the tundra and that it also controlled the timing and magnitude of melt water release to the basin.…”
Section: Overviewmentioning
confidence: 99%
“…The coupled model laterally routes excess surface runoff (that above a defined ponding depth) and subsurface runoff (water in excess of soil storage) from the vertical water budget through soils and stream channels to CLASS 3.6. MESH and its immediate predecessor, WATCLASS, have been successfully applied to several Canadian basins (Pohl et al, 2005;Davison et al, 2006;Pietroniro et al, 2007;Soulis and Seglenieks, 2007;Dornes et al, 2008;Yirdaw et al, 2009;MacLean et al, 2010).…”
mentioning
confidence: 99%